Impaired fasting glucose levels among perinatally HIV-infected adolescents and youths in Dar es Salaam, Tanzania - Nkinda, Lilian; Buberwa, Eliud; Memiah, Peter; Ntagalinda, Alieth; George, Martin; Msafiri, Frank; Joachim, Agricola; Majigo, Mtebe; Ramaiya, Kaushik; Sunguya, Bruno (Frontiers in Endocrinology, 2022)
Objective: This study assessed impaired fasting glucose and associated factors among perinatally HIV-infected youth in Dar es salaam Tanzania. Methods: This cross-sectional study was conducted among 152 youth attending HIV clinic at Muhimbili National Hospital and Infectious Disease Centre from July to August 2020. Fasting blood glucose (>8 hours) was measured using one-touch selects simple with an accuracy of 99.9%. We also examined C-Reactive Protein and interleukin-6 inflammatory biomarkers in relation to pre-diabetes. Comparison between groups were explored using Chi-square, and binary logistics was used to examine the associations between independent variables and the outcome Results: Of the 152 participants, the majority were male (n=83[54.6%]), and the mean age was 16±4.8 years. Overweight or obesity was prevalent in 16.4%, while more than one in ten (13.2%) had high blood pressure (≥149/90mmHg). All participants were on antiretroviral therapy (ART); 46% had used medication for over ten years, and about one in three had poor medication adherence. Among the recruited youths, 29% had impaired fasting glucose. Males were three times more likely to have IFG than females (OR, 2.7, 95% CI 1.28-5.71, p=0.009). Inflammatory biomarkers (C-Reactive Protein and Interleukin-6) were not significantly associated with IFG. Conclusion: About one in three perinatally HIV-infected youths had impaired fasting glucose in Dar es Salaam, Tanzania, with males bearing the biggest brunt. About a similar proportion had poor ART adherence. This calls for urgent measures to interrupt the progression to diabetes disease and prevent the dual burden of disease for this uniquely challenged population. Moreover, further efforts are also needed to address poor adherence to ART to avoid poor disease outcomes.